Power spectrum analysis of ionospheric fluctuations with the Murchison Widefield Array. Issue 7 (2nd July 2015) - Loi, Shyeh Tjing; Trott, Cathryn M.; Murphy, Tara; Cairns, Iver H.; Bell, Martin; Hurley‐Walker, Natasha; Morgan, John; Lenc, Emil; Offringa, A. R.; Feng, L.; Hancock, P. J.; Kaplan, D. L.; et al.
Abstract Low‐frequency, wide field‐of‐view (FOV) radio telescopes such as the Murchison Widefield Array (MWA) enable the ionosphere to be sampled at high spatial completeness. We present the results of the first power spectrum analysis of ionospheric fluctuations in MWA data, where we examined the position offsets of radio sources appearing in two data sets. The refractive shifts in the positions of celestial sources are proportional to spatial gradients in the electron column density transverse to the line of sight. These can be used to probe plasma structures and waves in the ionosphere. The regional (10–100 km) scales probed by the MWA, determined by the size of its FOV and the spatial density of radio sources (typically thousands in a single FOV), complement the global (100–1000 km) scales of GPS studies and local (0.01–1 km) scales of radar scattering measurements. Our data exhibit a range of complex structures and waves. Some fluctuations have the characteristics of traveling ionospheric disturbances, while others take the form of narrow, slowly drifting bands aligned along the Earth's magnetic field.